Experiences and long-term repercussions of perinatal grief in women after perinatal bereavement: a meta-ethnography - Beato, Beatriz Volpin Gomes; Machado-Kayzuka, Giovanna Cristina; Neris, Rhyquelle Rhibna; Payne, Elana; de Andrade Alvarenga, Willyane; Leite, Ana Carolina Andrade Biaggi; Silva-Rodrigues, Fernanda Machado; Polita, Naiara Barros; deMontigny, Francine; Silverio, Sergio A.; Nascimento, Lucila Castanheira (Frontiers in Psychiatry, 2025)
IntroductionPerinatal bereavement can profoundly disrupt maternal identity and is often accompanied by longer-term emotional suffering. Whilst immediate grief responses have been studied, less is known about how this experience evolves over time. This meta-ethnography aimed to synthesize qualitative evidence on the long-term experiences and repercussions of perinatal grief in women after a pregnancy loss.MethodsA systematic review of six databases was conducted. Primary qualitative studies were included if they addressed experiences occurring at least one year after a perinatal bereavement. A total of 2,253 records were screened, and 18 studies met the inclusion criteria. Data quality was assessed, and the data were subjected to an analytic synthesis using meta-ethnography.ResultsThree themes and six sub-themes were identified, revealing perinatal grief as a prolonged and transformative experience. Women reported emotional pain, identity disruption, and social silencing. In contrast, empathic care, sustained support, and social validation helped them reconstruct their identities. In line with meta-ethnographic approaches, a theory was developed: “The quietest of births cause the loudest anguish: Whilst some bereaved mothers walk a solitary path, those with broader support networks are more empowered, but both experience an intense change to The Self.”.DiscussionThese findings show grief is shaped not only by the loss itself but also by how it is acknowledged or silenced by healthcare systems and society. Gaps were identified regarding long-term grief during times of health system uncertainty and in cases of fetal malformation, revealing the need for further research and policy development.ConclusionSupportive and continuous care between lost and future pregnancies is essential to alleviate suffering and promote identity reconstruction among bereaved mothers facing long-term perinatal grief.